The Unbearable Stability of the German Wage Structure : Evidence and Interpretation - Prasad, Eswar (IMF Working Papers; Working Paper ;, 2000)
This paper uses micro data from the German Socio-Economic Panel to document that the wage structure in West Germany was remarkably stable during 1984-97, with little variation over time in wage or earnings inequality between and within different skill groups. Empirical evidence suggests that this stability is attributable to institutional factors rather than market forces. The rigidity of relative wages, despite relative shifts in labor demand that favor skilled workers, has resulted in sharp declines in employment rates for unskilled workers. The microeconomic evidence is shown to have important implications for interpreting trends in wage shares, capital-labor ratios, and aggregate unemployment.